Peningkatan Daya Saing UMKM Melalui Optimalisasi Penyusunan Laporan Keuangan di Magewair Production - Bruno, Andreas; Sanga, Konstantinus Pati; Yuneti, Katharina (Universitas Nusa Nipa Maumere, 2025)
This study aimed to analyze the enhancement of the competitiveness of the MSME Magewair Production through the optimization of financial statement preparation. As one of the key pillars of Indonesia’s economy, MSMEs often face challenges in financial management, particulary in preparing financial statements in accordance with accounting standards. The research employed a qualitative method with a case study approach, where data were collected through in-dept interviews with the management of Magewair Production and the analysis of existing financial statement documents. The results indicate that although Magewair Production has routinely carried out financial recording, the reports produced remain simple and have not complied with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The main constraints include a lack of accounting knowledge, limited technology, and insufficient training. Optimizing financial statement preparation can improve operational efficiency, access to funding, business growth, and the reputation and trust of stakeholders. This study recommends SAK EMKM training, the utilization of simple accounting technology, and guidance from government or academics to assist MSMEs such as Magewair Production in preparing better financial statements, thereby enhancing their competitiveness in the market.